SANCTIONS AGAINST CHILDREN WHO COMMIT CRIMINAL OFFENSE IN INDONESIA - Haeranah, Haeranah; Azisa, Nur; Soewondo, Slamet Sampurno; Nur, Rafika; Bakhtiar, Handina Sulastrina (Tadulako University, 2020)
In Indonesia the regulation of the age limit of children is very much regulated in various kinds of existing laws and regulations. related to the imposition of sanctions against children who commit a crime is regulated in detail in law no 11 of 2012 the Criminal Justice System for Children which regulates the age limit of children who can be sanctioned are children who have aged 12 (twelve) years, but have not yet age 18 (eighteen) years and for the types of sanctions imposed on children are divided into 2 types namely criminal sanctions and sanctions of actions.